The significance of cardiac inflammatory protocol of FDG PET-CT in the diagnosis and response assessment of tuberculous pericarditis: A case report - Kabilash Dhayalan; Harish Goyal; Dhanapathi Halanaik; Shaheer Ahamed (Asia Oceania Journal of Nuclear Medicine and Biology, 2025)
Tuberculous pericarditis (TBP) is a rare but potentially life-threatening manifestation of tuberculosis, often presenting with nonspecific symptoms and varied clinical features. The disease is characterised by inflammation of the pericardium due to mycobacterium tuberculosis, leading to complications such as effusion, tamponade, and, in chronic cases, constrictive pericarditis. TBP is associated with high mortality, particularly if not promptly diagnosed and treated. 18F-fluorodeoxyglucose positron emission tomography-computed tomography (18FDG PET-CT) has proven invaluable in diagnosing and managing TBP. This imaging modality allows for precise inflammatory activity localisation and differentiates TBP from other causes of pericardial disease. Additionally, the cardiac inflammation protocol of 18FDG PET-CT enhances imaging accuracy by suppressing the normal physiological FDG uptake in the myocardium. In this case report, we highlight the pivotal role of the cardiac inflammation protocol of 18FDG PET-CT in both the initial diagnosis and subsequent response assessment of TBP, underscoring its importance in clinical practice.